2017
DOI: 10.7185/geochemlet.1739
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decrease of MgAlO2.5 component in bridgmanite with pressure

Abstract: The solubility of the MgAlO 2.5 component in bridgmanite was measured at pressures of 27, 35 and 40 GPa and a temperature of 2000 o K using an ultra-high pressure multi-anvil press. Compositional analysis of recovered samples demonstrated that the MgAlO 2.5 component decreases with increasing pressure, and approaches virtually zero at 40 GPa. Above this pressure, the MgAlO 2.5 component, i.e. the oxygen-vacancy substitution, becomes negligible, and Al is incorporated in bridgmanite by the charge-coupled substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Previous studies demonstrated that Al 2 O 3 -rich bridgmanite transforms to the LN-type phase upon decompression at ambient temperature (Funamori et al, 1997;Ishii et al, 2017;Liu et al, 2016;Liu, Ishii, & Katsura, 2017;Liu, Dubrovinsky, et al, 2019;Miyajima et al, 1999). In situ XRD observations (Figure 4) demonstrate that the same phase transition occurs in the En 50 FA 50 sample.…”
Section: Phase Transition Of Bridgmanite To the Ln-type Phase Upon Dementioning
confidence: 52%
See 4 more Smart Citations
“…Previous studies demonstrated that Al 2 O 3 -rich bridgmanite transforms to the LN-type phase upon decompression at ambient temperature (Funamori et al, 1997;Ishii et al, 2017;Liu et al, 2016;Liu, Ishii, & Katsura, 2017;Liu, Dubrovinsky, et al, 2019;Miyajima et al, 1999). In situ XRD observations (Figure 4) demonstrate that the same phase transition occurs in the En 50 FA 50 sample.…”
Section: Phase Transition Of Bridgmanite To the Ln-type Phase Upon Dementioning
confidence: 52%
“…Journal of Geophysical Research: Solid Earth studies on K 0 of AlAlO 3 -bridgmanite (e.g., Zhang et al, 1999;Daniel et al, 2004;Yagi, et al, 2004;Walter et al, 2004Walter et al, , 2006, the reported data are highly scattered due to the strong variation of AlAlO 3 and MgAlO 2.5 components with pressure (Brodholt, 2000;Liu, Ishii, & Katsura, 2017), temperature (Brodholt, 2000;Liu, Akaogi, & Katsura, 2019), and Mg/Si ratio of the bulk composition (Andrault et al, 2001;Liu, Boffa Ballaran, et al, 2019) in the lower mantle. We therefore used dK 0 /dX = − 0.010 ± 0.003 GPa/mol for the AlAlO 3 component based on a theoretical study by Panero et al (2006).…”
Section: 1029/2019jb018447mentioning
confidence: 99%
See 3 more Smart Citations